Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12864-019-5889-5
|View full text |Cite
|
Sign up to set email alerts
|

About the existence of common determinants of gene expression in the porcine liver and skeletal muscle

Abstract: Background The comparison of expression QTL (eQTL) maps obtained in different tissues is an essential step to understand how gene expression is genetically regulated in a context-dependent manner. In the current work, we have compared the transcriptomic and eQTL profiles of two porcine tissues (skeletal muscle and liver) which typically show highly divergent expression profiles, in 103 Duroc pigs genotyped with the Porcine SNP60 BeadChip (Illumina) and with available microarray-based measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…In humans, significant commonalities of sQTL between tissues and of geQTL between tissues were reported [ 57 , 58 ]. Recent studies have suggested that, in cattle, three types of eQTL (sQTL, eeQTL and geQTL) were shared between tissues [ 12 ] and that, in pig, geQTL were extensively shared between liver and muscle [ 59 ]. Our results support the extensive sharing of all eQTL types between liver and muscle, but disagree with other studies [ 47 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, significant commonalities of sQTL between tissues and of geQTL between tissues were reported [ 57 , 58 ]. Recent studies have suggested that, in cattle, three types of eQTL (sQTL, eeQTL and geQTL) were shared between tissues [ 12 ] and that, in pig, geQTL were extensively shared between liver and muscle [ 59 ]. Our results support the extensive sharing of all eQTL types between liver and muscle, but disagree with other studies [ 47 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have for the first time systematically catalogued eQTL in equine skeletal muscle, both at rest and post-exercise. Previous investigations of eQTL in skeletal muscle have focussed primarily on human T2D (Sharma et al, 2011; Keildson et al, 2014a; Sajuthi et al, 2016; Langefeld et al, 2018) and meat quality traits in production animals (Ponsuksili et al, 2015; Gonzalez-Prendes et al, 2017; Pampouille et al, 2018; Gonzalez-Prendes et al, 2019; Velez-Irizarry et al, 2019). Our investigation of eQTL in the context of skeletal muscle and exercise present some of the only work to-date in this area (Kelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have for the first time systematically catalogued eQTL in equine skeletal muscle, both at rest and post-exercise. Previous investigations of eQTL in skeletal muscle have focussed primarily on human T2D (Sharma et al, 2011; Keildson et al, 2014a; Sajuthi et al, 2016a; Langefeld et al, 2018)and meat quality traits in production animals (Ponsuksili et al, 2015; Gonzalez-Prendes et al, 2017; Pampouille et al, 2018; Gonzalez-Prendes et al, 2019; Velez-Irizarry et al, 2019). Our investigation of eQTL in the context of skeletal muscle and exercise present some of the only work to-date in this area (Kelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%